Pengembangan E-Book Berjenis E-Flip PDF Dengan Belajar Mandiri Terbimbing Berbasis Problem Posing Menggunakan Ide Kreatif Scamper - Rino, Rino; Reni Astuti; Muchtadi , Muchtadi (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this study was to develop a valid, practical and effective E-Book learning media of E-Flip PDF with Guided Self-Learning on student learning outcomes on matrix material in class XI of SMA Negeri 1 Nanga Mahap. The method used is a 4D research method which is limited to Define, Design and Develo. The subjects in this study were 29 students of class XI SMA Negeri 1 Nanga Mahap, 3 material and media experts. The instruments used in this research are in the form of material expert validation sheets and media expert validation sheets, teacher response questionnaires, student response questionnaires and posttest questions based on the results of research that have been carried out, the results of the validation of the E-Book learning media are E-Flip PDF with Independent Learning. Supervised has a level of validity of 93.66% with very valid criteria, the level of practicality of learning media is 89.93% with very practical criteria and the effectiveness level of learning media is 82.75% with very effective criteria.